Mastitis caused by Bacillus anthracis in a beef cow - Hawkes, Ross (Canadian Veterinary Medical Association, 2008)
A mixed-breed beef cow was presented with swelling of the front and hind left quarters of the mammary gland and mild depression. Direct examination and culture of the serosanguinous-like milk samples collected from these quarters were consistent with Bacillus anthracis infection.